Associated Factors in Willingness to Shift Tobacco Expenditure Into National Health Insurance Premium Among Subsidized Members - Wahidin, Mugi; Mikrajab, Muhammad Agus; Agustiya, Rozana Ika; Azteria, Veza (Kesmas, 2025)
In Indonesia, subsidized members are the largest group in the National Health Insurance program. Hence, it is essential to understand their ability to pay (ATP) based on tobacco expenditure. This study aimed to determine the ATP of subsidized members based on tobacco expenditure and factors associated with their willingness to pay (WTP). This cross-sectional study used secondary data from the National Institute of Health Research and Development. The population included all subsidized members; 19,918 were sampled for ATP, and 14,560 were WTP. The independent t-test, ANOVA, and logistic regression were performed. Results showed that ATP from tobacco expenditure ranged from USD 4 to 4.8, higher than the minimum monthly payment, and WTP ranged from USD 0.1 to 1.2. About 73.6% of respondents preferred to pay less than USD 0.3 as an additional payment, while 3.5% were willing to pay more than USD 1. The ATP was higher than the monthly payment and WTP, but only a few were willing to be non-subsidized members. Factors associated with WTP were sex, age, education level, family member, occupation, expenditure, and history of health facility utilization, implying the subsidized members should be reviewed, especially among smokers.